THE EFFECT OF LEARNING CYCLE MODEL ASSISTED BY SELF-ASSESSMENT ON STUDENTS’ WRITING COMPETENCY AT EFL STUDENTS IN SMP SARASWATI 1 DENPASAR - Candra Dewi, I Gusti Ayu Agung Ida Ratna (LPPM Undiksha, 2020)
This study aimed to investigate the implementation and the effect of learning cycle model assisted by self-assessment on the eighth grade students in SMP Saraswati 1 Denpasar in the academic year 2018/2019. The population was 294 students. The sample was 82 students selected by using a random sampling technique. This research used a mixed method design. The quantitative design used a posttest-only control group design and the qualitative design used descriptive qualitative design. The result of the t-test showed that the sig. (2 tailed) value was 0.000 ? 0,05. The mean score of the experimental group was 88.20 and the control group was 79.12. It can be concluded that writing competency of the experimental group was higher than the control group. This result was justified by the result of the observation checklist which showed that the implementation of learning cycle model assisted by self-assessment was very good.